(3CQLhRI aj TQM GdfZeGJs - (3YHO Gddg Hf Ndjd Hf jhSa, LeGd GdOjf GdeGQOGfj,J (B809 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYdje GdYGde ebSe GdYbhd jfi GdYGde eejR GdCdSf hGddZGJ hhGgH GdGfZGe GdCUhGJ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B57 - (3U(B65s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B85 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B53s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B46 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK GSJGfHhd (B(2130(1)) s
Keywords: (3GdehSjbi hGdZfGAs